2014
DOI: 10.1007/s12070-014-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Long-term Neurocognitive Outcome in Patients with Obstructive Sleep Apnea Syndrome After Continuous Positive Airway Pressure Treatment

Abstract: Neurocognitive dysfunction is a major clinical consequence in patients with obstructive sleep apnea syndrome (OSAS). The effects of continuous positive airway pressure (CPAP) treatment, as the gold standard of treatment in OSAS, on this major complication are controversial. The duration and compliance of CPAP are thought to be important factors but evidence is lacking. This study is designed to evaluate the effects of immediate (one night), long-term (3 months) influence and the compliances of CPAP treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Diagnostic polysomnography was performed in accordance with previous studies and recommendations. 28,29 Sleep staging and respiratory events were determined using standardized definitions. 30 Polysomnography scoring was performed by experienced accredited sleep technologists.…”
Section: Polysomnographymentioning
confidence: 99%
“…Diagnostic polysomnography was performed in accordance with previous studies and recommendations. 28,29 Sleep staging and respiratory events were determined using standardized definitions. 30 Polysomnography scoring was performed by experienced accredited sleep technologists.…”
Section: Polysomnographymentioning
confidence: 99%
“…In our population, average compliance rate was intermediate (5,1 ± 0.37 h per night). While some neurocognitive functions could benefit from PAP immediately after the beginning of the treatment, additional improvements in other neurocognitive domains might necessitate extended PAP treatment with good clinical compliance for patients with severe OSA ( Lin et al, 2015 ). It was shown that one month of PAP treatment in patients with OSA leads to reduced daytime sleepiness and improved verbal episodic memory ( Rosenzweig et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPAP has been shown to overcome sleep-related symptoms and increase quality of life ( Laratta et al, 2017 ). Cognitive functions, e.g., visual ( Lin et al, 2015 ) and short-term memory ( Canessa et al, 2011 ), seem to be partially restored by standard OSA treatment such as positive airway pressure (PAP), but the reversibility of OSA-related deficits in verbal memory following PAP treatment needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%